Fantasy: Exploring Moral Values in Barbie Movie 2023 - Nurridzka Fadyaramadhani; Nirwan Nirwan; Hilda Sari Wardhani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This article demonstrates how moral values are presented in this movie. The aim is to uncover the kinds of morality performed by the characters. The writer applies semiotics as a tool for analysis to interpret the texts used by them. The results reveal two central moral values: moral conflict arises in decision-making, while moral responsibility can be observed in the context of relationships among the characters and the place called 'Barbie Land' where they live.